‘Community voices, curatorial choices’: community consultation for the 1807 exhibitions - Fouseki, Kalliopi (Museum and Society, 2015)
This paper argues that community consultation is not always a democratic process as power often resides with museum staff members who decide which community views to accept and which to ignore. Drawing upon a series of semi structured interviews with community members, community officers, curators and other museum staff as part of the 1807 Commemorated project, I attest that consultative group members often experienced frustration, anger, and disappointment during and after the development of the 1807 exhibitions. These emotions were primarily driven by the communities’ unmet needs and expectations as well as by a clash between object-centric curatorial choices and people oriented community voices; members of the African-Caribbean community viewed their participation in the consultation meetings both as a means of empowerment of their communities and as a gesture of acknowledgement, social justice and recognition. Thus, it is imperative that community consultation is replaced by active negotiation and engagement that is aimed at shared power and ownership.